Pesticides properties in the environment with a diskette - Hornsby, Arthur G (Springer-Verlag, 1996)
This book and diskette provide a unique database compiled from extensive literature searches on pesticide properties in the environment. It presents data on hundreds of pesticides, including: Names (common, commercial, and scientific); Chemical formulas and CAS numbers; Environmental fate properties (water solubility, field half-life, sorption coefficient, vapor pressure, dissociation constants)